Association of alcohol consumption with abortion among ever-married reproductive age women in Ethiopia: A multilevel analysis - Ayana, Galana Mamo; Raru, Temam Beshir; Deressa, Alemayehu; Regassa, Lemma Demissie; Gamachu, Mulugeta; Negash, Belay; Birhanu, Abdi; Merga, Bedasa Taye (Frontiers in Global Women's Health, 2022)
Abstract Background: Abortion which is also called a miscarriage or spontaneous abortion before the 20th week. Even though, many guidelines advice that pregnant women should avoid drinking alcoholic beverages during all stages of pregnancy, Alcohol consumption-related to Abortion among pregnant women was prevalent. However, there is the dearth of articles about the impact of Alcohol consumption-related on pregnancy loss. Therefore, the current study was aimed assess the impact of alcohol consumption on abortion among pregnant women in Ethiopia. Methods: Secondary data analysis was conducted among pregnant women in Ethiopia using the most recent Ethiopian Demographic and Health Survey (EDHS) reports. A total of 11,396 reproductive age women aged 15–49 years were included in this study. Descriptive statistics were conducted to describe the study population. The Multi-level binary logistic regression model was used to take in to account the variability. The impact of alcohol consumption on abortion was estimated using Multi-level binary logistic model by considering confounders. Variables with a p-value of <0.05 in the multivariable analysis were identiﬁed as statistically signiﬁcant of response variable. Results: The proportion of women who had Abortion was 10.46% with 95% CI (9.92, 11.03). In the ﬁnal model of the multi-level analysis age group (AOR = 6.13; 95% CI; 3.86-9.73), Education levels (AOR = 1.29; 95 and CI; 1.10-1.51), Alcohol consumers (AOR = 1.38; 95% CI; 1.18-1.61), Age at first sex (AOR = 1.20; 95% CI; 1.03-1.39), Media exposure (AOR═1.28, CI: 1.10-1.48), Contraceptive use (AOR ═ 1.34, CI: 1.16-1.56), Occupation of respondent’s (AOR═1.21, CI: 1.06-1.38) were identified to be significant determinants of abortion in Ethiopia. Conclusion: Sexual and reproductive health education, and family planning programs should target older women in reproductive age group, women with primary educational status, working women, and those who initiated sexual intercourse at a younger age considering it could reduce abortion and unintended pregnancy. Furthermore, as part of sexual and reproductive health education, the adverse effect of alcohol consumption on abortion should be emphasized.